(3x^3 - 2x^2 + 3x - 2) : (x^2 + 1) cứu sắp thii
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/+b/\(A\left(x\right)=2x^5+2-6x^2-3x^3+4x^5\)
\(=\left(2x^5+4x^5\right)-3x^3-6x^2+2\)
\(=6x^5-3x^3-6x^2+2\)
c/Bậc của \(A\left(x\right)\) là 5
d/\(A\left(1\right)=6\cdot1^5-3\cdot1^3-6\cdot1^2+2\)
\(=6-3-6+2\)
\(=-1\)
\(A\left(-2\right)=6\cdot\left(-2\right)^5-3\cdot\left(-2\right)^3-6\cdot\left(-2\right)^2+2\)
\(=6\cdot\left(-32\right)-3\cdot\left(-8\right)-6\cdot4+2\)
\(=-192-\left(-24\right)-24+2\)
\(=-190\)
a) và b)
A(x) = 2x⁵ + 2 - 6x² - 3x³ + 4x⁵
= (2x⁵ + 4x⁵) - 3x³ - 6x² + 2
= 6x⁵ - 3x³ - 6x² + 2
c) Bậc của A(x) là 5
d) A(1) = 6.1⁵ - 3.1³ - 6.1² + 2
= 6.1 - 3.1 - 6.1 + 2
= 6 - 3 - 6 + 2
= -1
A(2) = 6.2⁵ - 3.2³ - 6.2² + 2
= 6.32 - 3.8 - 6.4 + 2
= 192 - 24 - 24 + 2
= 146
a: \(\dfrac{4x^4+3x^3}{-x^3}+\dfrac{15x^3+6x}{3x}=0\)
\(\Leftrightarrow-4x-3+5x^2+2=0\)
\(\Leftrightarrow5x^2-4x-1=0\)
\(\Leftrightarrow5x^2-5x+x-1=0\)
=>(x-1)(5x+1)=0
=>x=1 hoặc x=-1/5
b: \(\dfrac{x^2-\dfrac{1}{2}x}{2x}-\dfrac{\left(3x-1\right)^2}{3x-1}=0\)
\(\Leftrightarrow\dfrac{1}{2}x-\dfrac{1}{4}-3x+1=0\)
\(\Leftrightarrow\dfrac{-5}{2}x+\dfrac{3}{4}=0\)
\(\Leftrightarrow-\dfrac{5}{2}x=-\dfrac{3}{4}\)
hay \(x=\dfrac{3}{4}:\dfrac{5}{2}=\dfrac{3}{4}\cdot\dfrac{2}{5}=\dfrac{6}{20}=\dfrac{3}{10}\)
1: \(\dfrac{2x^3+11x^2+18x-3}{2x+3}\)
\(=\dfrac{2x^3+3x^2+8x^2+12x+6x+9-12}{2x+3}\)
\(=x^2+4x+3-\dfrac{12}{2x+3}\)
a: \(P\left(x\right)=3x^2-x-1\)
\(Q\left(x\right)=-3x^2-4x-2\)
b: \(G\left(x\right)=3x^2-x-1+3x^2+4x+2=6x^2+3x+1\)
c: Để G(x)-6x-1=0 thì 6x2-3x=0
=>3x(2x-1)=0
=>x=0 hoặc x=1/2
\(=\dfrac{3x\left(x^2+1\right)-2\left(x^2+1\right)}{x^2+1}=3x-2\)